Optimization of integrated bee agro-tourism marketing system at KTH Pasir Madu Ciparigi village, Sukadana district, Ciamis regency - Faruk, Mujaddid; Romansyah, Romdah; Firdaus, Hendra (Galuh International Journal of Community Service and Development, 2025)
The purpose of the Community Service (PKM) "Optimization of Integrated Bee Agro-tourism Marketing System at Pasir Madu Forest Farmer Group (KTH) Ciparigi Village, Sukadana District, Ciamis Regency" is to boost productivity, expand the marketing of Pasir Madu KTH products, and provide facilities for bee farming agro-tourism. It also aims to address the issues of non-optimal marketing and a lack of facilities for bee farming agro-tourism. Its output might include pieces in print and electronic mass media, YouTube videos, articles in The National Journals, and increased partner revenue. The method used in implementing this PKM is the instructional method, followed by practice which includes five stages, namely: 1) Delivery of information (socialization/counseling) to Pasir Madu KTH administrator in Ciparigi Village, 2) Training on marketing system for bee products 3). Mentoring and evaluation in the form of Management and Promotion of tourism through leaflets, posters, and social media as well as marketing evaluation 4) Sustainability of the program through Seminars on the results of community service activities and ongoing mentoring. The results achieved by the Pasir Madu KTH Administrator were an increase in knowledge about optimizing bee product marketing by 25%, as well as management of beekeeping agro-tourism facilities by 30%, and the community around Pasir Madu KTH received an additional source of income of 35% due to the existence of beekeeping agro-tourism.